One country, three colonial legacies: the politics of colonialism, capitalism and development in the pre- and post-colonial Cameroon - Lekane, Gillo Momo; Asuelime, Lucky (Faculty of Humanities, University of the Free State, 2017)
Cameroon is usually misconceived of as a former French colony due to its geographical location which is at the intersection of what used to be called French West Africa and French Equatorial Africa. This misconception clouds the country’s triple colonial heritage that has shaped and continues to shape Cameroon’s historical path and its agro-political landscape. The colonial heritage of Cameroon contributes to an understanding of key socio-economic, political and developmental challenges the country has been facing and continues to face. This article discusses the history of Cameroon’s early contacts with Europeans (Germans, French and British in particular) and how these encounters influenced and shaped the country’s economic history. It highlights how colonialism was a vehicle used to incept capitalism in the country with an emphasis on cash crop farming. The article also discusses the legacy of these heritages and the strategies that were successively adopted to address economic development challenges.
Keywords: Cameroon; Colonialism; Coffee farming; Development; Capitalism; Economic development